Masjid dan Aktivitas Dakwah di Era Revolusi Industri 4.0 - Slamet Untung (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The problems discussed in this research are how the existence and function of mosque in supporting da‟wah activities in Industrial Revolution 4.0 are. This research is a library study focusing on discussion about mosque as an Islamic da‟wah institution in supporting da‟wah activities in Industrial Revolution 4.0 era. The primary data covers scientific works about mosque as a da‟wah institution, while the secondary data covers various works about mosque, da‟wah, and Industrial Revolution. Qualitative approach is used in this study. The collected data is analyzed using content analysis method by reducing, displaying, and verifying the data. The result of this study finds that the existence and function of mosque is increasingly needed by Muslims community in Industrial Revolution 4.0 era. Mosque for Muslims is likened as water for fish. Muslims cannot “live” without “existence” of mosque. However, mosque is now like poisoned water, which led to da‟wah crisis befalling Muslims community these days. Muslims community is responsible to elevate mosque to the higher position since the challenge of this era is extremely heavy. One of the ways is utilizing the technology, especially information technology. It can be implemented by giving training activities, such as computer, internet, or other social media training, for mosque caretaker for the sake of the mosque and da‟wah activities.